Juvenilização na educação de jovens e adultos no ensino médio : um estudo de caso no município de Salvador Bahia - Afro, Luana Leão (2016)
Progressively we have seen the multiplication of the presence of young people between 15 and 24 years enrolled in the form of Youth and Adult Education (EJA) and this continued growth has characterized the juvenilisation phenomenon of Youth and Adult Education in High School. Understanding this process is the central objective of the work. This study seeks to understand what has interfered so that young people leave the regular education entering the EJA modality. In this perspective, it has been a challenge for teachers, in view of the diversity not just age, above all, about the literacy levels and realities of the public this sport. So to analyze the research phenomenon sought to define the profile of these young people, their experiences and life trajectories, identifying the motivations that led young people to drop out of mainstream education and join the Youth and Adult Education MS. In addition the study also aims to identify together with the teachers of this type of education which the main difficulties faced due to juvenilisation experienced in EJA MS. The empirical field research was a Night Centre public schools located in Salvador (Bahia), more precisely in the neighborhood of Oil Palm (Lesser Town). The theoretical-methodological approach adopted was the case study of quantitative quality approach option. As methodological instruments, made use of the questionnaire, Semi-structured interview and document analysis.